Ethics of who am I? to how should I live? Ethics before modernity - Torres Parra, Gianmarco Rubens (2025)
The general question that guides this article is: what do we do with our responsibility to others? We can say that our worry is due to ethics, but in the context previous to modernization. Before we ask ourselves, howto get to a good living (as a responsibility to others), it is fundamental that we revisit the question : who am I? For example, it is the way of knowing yourself that Anselmo considers in «El Proslogion». On this, ethics is comprehended by how much you know yourself; and about ethics that are brought by intrinsically motivation.